The Influence of Service Innovation and Customer Experience on Repurchase Intentions - Maya Handayani; Mahlia Muis; Muhammad Toaha (Hasanuddin Journal of Business Strategy, 2022)
The rapid growth of fast-food restaurants has resulted in the opening of various fast-food restaurant locations in Makassar, which shows the increasingly competitive fast-food industry. When customers consume and spend a long time in fast food restaurants will affect customer repurchase intentions; service innovation and customer experience become the most important predictors of customer behavior. This study aims to determine the effect of service innovation and customer experience on the repurchase intention of McDonald's Hertasning Makassar consumers. The type of research used is descriptive quantitative. With a total number of voluntary participants, 154 respondents. The data analysis technique was used using multiple regression analysis with computer software tools SPSS 25 for Windows. The study results that service innovation can be used to predict repurchase intention. Differently, customer experience did not affect repurchase intention.